2010
DOI: 10.4161/org.6.3.12392
|View full text |Cite
|
Sign up to set email alerts
|

Development, characterization and clinical use of a biodegradable composite scaffold for bone engineering in oro-maxillo-facial surgery

Abstract: We have developed a biodegradable composite scaffold for bone tissue engineering applications with a pore size and interconnecting macroporosity similar to those of human trabecular bone. The scaffold is fabricated by a process of particle leaching and phase inversion from poly(lactideco-glycolide) (PLGA) and two calcium phosphate (CaP) phases both of which are resorbable by osteoclasts; the first a particulate within the polymer structure and the second a thin ubiquitous coating. The 3-5 μm thick osteoconduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0
6

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 13 publications
1
47
0
6
Order By: Relevance
“…Comprehensive in vitro and in vivo studies have demonstrated the positive influence of biomimetic apatite coating on the proliferative and osteoconductive properties of PLGA scaffolds (Davies et al 2010). A comprehensive review was compiled by Kretlow and Mikos (Kretlow and Mikos 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive in vitro and in vivo studies have demonstrated the positive influence of biomimetic apatite coating on the proliferative and osteoconductive properties of PLGA scaffolds (Davies et al 2010). A comprehensive review was compiled by Kretlow and Mikos (Kretlow and Mikos 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, we have shown in different studies that HUCPVCs can contribute to bone [25], cartilage [14], and dermal tissue [26] in vivo, and thus it may be reasonable to expect that the collagen expression data in this study would have reflected some synthetic activity in vivo. Indeed, the change from ovoid to elongated morphology by 30 days could be indicative of tenocytic differentiation, although our primers for decorin, tenomodulin, and tenascin-C were unable to distinguish between the human and rat tenocyte phenotypes.…”
Section: Hucpvcs Survive Xenogeneic Transplant and Express Collagenmentioning
confidence: 79%
“…The green line shows publications for laser surgery, chosen as a 'control' for the general gentle rise in medical publication. This graph was obtained by performing a PubMed search using the termthe formation of a collagen pattern in the shape of a human nipple [15], the formation of functional heart valves [16], reconstruction of cartilage [17], bone [18], oesophagus [19] and bladder wall [20]. In a variation on that theme, the engineering of structures that already incorporate cells in situ has been used to produce functional heart tissue [21].…”
Section: Figurementioning
confidence: 99%